Coupled swelling and nematic reordering in liquid crystal gels. Issue 43 (12th October 2017) - Lucantonio, Alessandro; DeSimone, Antonio
Abstract : Nematic–isotropic phase transition and swelling occur on separate time scales. A nematic microswimmer exploits this concept to change shape non-reciprocally. Abstract : We derive a multiphysics model that accounts for network elasticity with spontaneous strains, swelling and nematic interactions in liquid crystal gels (LCGs). We discuss the coupling among the various physical mechanisms, with particular reference to the effects of nematic interactions on chemical equilibrium and that of swelling on the nematic–isotropic transition. Building upon this discussion and using numerical simulations, we explore the transient phenomena involving concurrent swelling and phase transition in LCGs subject to a temperature change. Specifically, we demonstrate separation in time scales between solvent uptake and phase change, in agreement with experiments, which determines a kinetic decoupling between shape and volume changes. Finally, we discuss possible applications in the context of microswimmers, where such a kinetic decoupling is exploited to achieve non-reciprocal actuation and net motion in Stokes flow.